2017
DOI: 10.3390/ht6040018
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Ultrasensitive Procalcitonin Sandwich Immunoassay

Abstract: Procalcitonin (PCT) is well established as a highly specific biomarker for the detection of bacterial infections and sepsis. However, the currently available diagnostic tests are not able to detect very low or very early increases of PCT or even baseline levels in healthy individuals or patients with non-bacterial infections. In order to be able to detect these very low concentrations of PCT, a sandwich immunoassay was developed using high sensitivity Single Molecule Array technology (Simoa). The assay was tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…In the present study, the optimum cut-off value in the diagnosis of IA was > 260 pg/mL for PCT. Our data like other studies [ 8 , 28 , 29 ] showed a low elevation of PCT in patients with IA. The PCT level in patients with IA is lower because Aspergillus species have a tendency for local infection and isolation of this organism from the blood is rare [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the optimum cut-off value in the diagnosis of IA was > 260 pg/mL for PCT. Our data like other studies [ 8 , 28 , 29 ] showed a low elevation of PCT in patients with IA. The PCT level in patients with IA is lower because Aspergillus species have a tendency for local infection and isolation of this organism from the blood is rare [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…In Robinson et al, after 3 days, a PCT level > 500 pg/mL occurred in 81% (17/21) of the patients with invasive fungal diseases [ 28 ]. The mean PCT concentration in 86 healthy individuals was reported at 15.8 pg/mL by Carcamo and coworkers [ 29 ]. Also, in healthy people, PCT concentration was reported below 50 pg/mL (0.05 ng/ml] [ 29 ] and 100 pg/mL (< 0.1 ng/ml) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the detection methods reported to IL-6 and PCT mainly include enzyme-linked immunoassay(ELISA) [19], chemiluminescent immunoassay(CLIA) [20], lateral flow immunoassays (LFIA) [21], electrochemiluminescence immunofluorescence analysis [22], immunofluorescence amplification luminescence proximity homogeneous assay (AlphaLISA)technology [23] and high-sensitivity single molecule array technology (Simoa) [24] etc. ELISA requires a large amount of time, cost, machinery and professional training; chemiluminescence detection equipment is expensive and has a narrow linear range; and most of the techniques are limited to single-molecule detection, which lacks the efficiency of disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%